2021
DOI: 10.1080/15384101.2021.1909242
|View full text |Cite
|
Sign up to set email alerts
|

BZW1 promotes cell proliferation in prostate cancer by regulating TGF-β1/Smad pathway

Abstract: Background Recently, basic leucine zipper and the W2 domain-containing protein 1 (BZW1) is reported to be implicated in tumor progression. However, the role of BZW1 in prostate cancer remains unknown. This study is aimed to investigate the expression of BZW1 and its in uence on cell proliferation in prostate cancer.Methods The expression levels of BZW1 were measured in 136 cases of prostate cancer and matched adjacent non-cancerous prostate tissues by quanti cational real-time polymerase chain reaction (qRT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…[27] BZW1, a member of the bZIP transcription factor superfamily, is involved in the progression of multiple tumors. Shi et al [28] found that highly expressed BZW1 can significantly promote the proliferation of prostate cancer cells by regulating the TGF-β1/Smad pathway. Another study [29] showed that BZW1 and BZW2 are expressed in a variety of cancer types, but BZW1 has a more significant clinicopathological value, and its high expression has poor prognosis in lung adenocarcinoma, and its downregulation can inhibit lung adenocarcinoma metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…[27] BZW1, a member of the bZIP transcription factor superfamily, is involved in the progression of multiple tumors. Shi et al [28] found that highly expressed BZW1 can significantly promote the proliferation of prostate cancer cells by regulating the TGF-β1/Smad pathway. Another study [29] showed that BZW1 and BZW2 are expressed in a variety of cancer types, but BZW1 has a more significant clinicopathological value, and its high expression has poor prognosis in lung adenocarcinoma, and its downregulation can inhibit lung adenocarcinoma metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…BZW1 and BZW2 have been established to promote the malignant progression of several cancers. Shi et al indicated that BZW1 overexpression could promote prostate cancer cell proliferation by regulating TGF-β/Smad pathway ( Shi et al, 2021 ). Jin et al showed that overexpression of BZW2 in hepatocellular carcinoma cells significantly stimulated the activation of PI3K/AKT/mTOR pathway ( Jin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that BZW1 is highly expressed in cancer tissues and cell lines such as prostate cancer and lung adenocarcinoma 14 , 41 , 42 . BZW1 can promote cell proliferation in prostate cancer by regulating the transforming growth factor-beta1 (TGF-β1)/SMAD pathway 42 . Considering that some of the Bzw1 RNAi embryos were arrested at the cleavage stage (Fig.…”
Section: Discussionmentioning
confidence: 99%